On applications of iteration algorithms and Skorobagatko’s branching fractions to approximation of roots of polynomials in Banach algebras - Kopach, M.I.; Obshta, A.F.; Shuvar, B.A. (Carpathian Mathematical Publications, 2010)
Iteration algorithms for approximate factorization of some classes of polynomials with coefficients from a Banach algebra are investigated. These algorithms may be considered as methods of construction of analogues of V.Ya. Skorobagatko's branching fractions in Banach algebras.